Young adulthood and adulthood adiposity in relation to incidence of pancreatic cancer: a prospective study of 0.5 million Chinese adults and a meta-analysis - Pang, Y; Holmes, M; Kartsonaki, C; Guo, Y; Yang, L; Bian, Z; Chen, Y; Bragg, F; Iona, A; Millwood, I; Chen, J; Li, L; et al. (BMJ Publishing Group, 2017)
Background: Adult adiposity is positively associated with pancreatic cancer in Western populations. Little is known, however, about the association in China where many have lower BMI or about the relevance of young adulthood adiposity for pancreatic cancer in both Western and East Asian populations. Methods: The China Kadoorie Biobank recruited 512,000 adults aged 30-79 years during 2004-08, recording 595 incident cases of pancreatic cancer during 8 years follow-up. Cox regression yielded adjusted hazard ratios (HRs) for pancreatic cancer associated with self-reported young adulthood (mean ~25 years) body mass index (BMI) and with measured adulthood (mean ~52 years) BMI and other adiposity measures (e.g. waist circumference [WC]). These were further meta-analysed with published prospective studies. Results: Overall the mean BMI (SD) was 21.9 (2.6) at age 25 and 23.7 (3.3) kg/m2 at age 52. Young adulthood BMI was strongly positively associated with pancreatic cancer in CKB (adjusted HR=1.36, 95% CI 1.16-1.61, per 5 kg/m2 higher BMI) and in meta-analysis of CKB and 4 other studies (1.18, 1.12-1.24). In CKB, there was also a positive association of pancreatic cancer with adulthood BMI (1.11, 0.97-1.27, per 5 kg/m2), similar in magnitude to that in meta-analyses of East Asian studies using measured BMI (n=2; 1.08, 0.99-1.19) and of Western studies (n=25; 1.10, 1.06-1.12). Likewise, meta-analysis of 4 studies, including CKB, showed a positive association of adulthood WC with pancreatic cancer (1.10, 1.06-1.14, per 10 cm). Conclusions: In both East Asian and Western populations, adiposity was positively associated with risk of pancreatic cancer, with a somewhat stronger association for young than late life adiposity.